2020
DOI: 10.1186/s40545-020-00233-3
|View full text |Cite
|
Sign up to set email alerts
|

Sale of WHO AWaRe groups antibiotics without a prescription in Pakistan: a simulated client study

Abstract: Introduction Resistant strains of bacteria are rapidly emerging with increasing inappropriate use of antibiotics rendering them less efficacious. Self-purchasing of antibiotics particularly for viral infections is a key driver of inappropriate use, especially in lower- and middle-income countries. There is a particular issue in countries such as Pakistan. Consequently, there is a need to assess current rates of self-purchasing especially for reserve antibiotics to guide future policies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 75 publications
3
67
0
Order By: Relevance
“…Other strategies may though be needed to reduce inappropriate dispensing of antimicrobials. These include greater education in pharmacy school to address information gaps regarding antimicrobials and antimicrobial resistance (AMR), developing and implementing national guidelines for the management of infectious diseases typically seen in ambulatory care acknowledging the WHO AWaRe list of antibiotics, as well as monitoring community pharmacists’ activities through for instance mobile technologies ( Markovic-Pekovic et al, 2017 ; Hoxha et al, 2018 ; Kalungia and Godman, 2019 ; Saleem et al, 2019 ; Saleem et al, 2020 ). Community pharmacists should be mindful though that it can be difficult in practice to differentiate respiratory tract infections from COVID-19 among patients presenting with coughs and fever ( Ongole et al, 2020 ), and they should encourage testing and referrals where there are concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Other strategies may though be needed to reduce inappropriate dispensing of antimicrobials. These include greater education in pharmacy school to address information gaps regarding antimicrobials and antimicrobial resistance (AMR), developing and implementing national guidelines for the management of infectious diseases typically seen in ambulatory care acknowledging the WHO AWaRe list of antibiotics, as well as monitoring community pharmacists’ activities through for instance mobile technologies ( Markovic-Pekovic et al, 2017 ; Hoxha et al, 2018 ; Kalungia and Godman, 2019 ; Saleem et al, 2019 ; Saleem et al, 2020 ). Community pharmacists should be mindful though that it can be difficult in practice to differentiate respiratory tract infections from COVID-19 among patients presenting with coughs and fever ( Ongole et al, 2020 ), and they should encourage testing and referrals where there are concerns.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Drug Act 1967 of Pakistan, dispensing antibiotics without a valid prescription is prohibited; however, the irrational dispensing of antibiotics is widespread [ 6 , 31 ]. Many studies from Pakistan have reported that pharmacists and pharmacy technicians routinely dispense antibiotics without inquiring about a prescription [ 32 , 33 , 34 ]. The respondents of our study righty pointed out that non-compliance to regulations often permits the purchase of antibiotics without a prescription from community pharmacies.…”
Section: Discussionmentioning
confidence: 99%
“… 107 , 108 In addition, the development and dissemination of the WHO AWaRe list of antibiotics to improve future antibiotic prescribing and dispensing. 109 , 110 Engineering includes organizational or managerial interventions such as instigating and monitoring prescribing targets and quality targets. 99 , 100 Quality targets could include the percentage of antibiotics prescribed according to agreed guidance, the percentage of antibiotics prescribed within a specified time and for an agreed length to prevent SSIs, as well as monitoring drug and therapeutic committee (DTC) activities against agreed performance indicators.…”
Section: Methodsmentioning
confidence: 99%